Social Computing Research Center - (:unkn) unknown (My University, 2026)
The Social Computing Research Center at the Cyprus University of Technology (CUT) is a multidisciplinary center aiming to advance research on various aspects of Social Computing. The Center addresses the key societal challenges outlined in Horizon 2020 and Horizon Europe, which among others include: inclusive, innovative and secure societies (including cyber-security) information and communication technologies alignment of society (including societal actors such as researchers, citizens, policy makers, business, third sector organizations, etc.) with research and innovation process seizing ICT opportunities to engage society in its research and innovation activities sustainable economies and societies through new digital technologies This research unit’s topic is novel and unique, both in Cyprus and internationally. SCRC focuses on the intersection of Computing and Social Sciences addressing key societal challenges. Although social computing is being investigated by other groups in Cyprus and internationally, this is often done mono-thematically within one department or rarely as a collaboration between two universities or two departments. In our case, the issues are studied in a holistic way involving researchers from various CUT departments and with various backgrounds (e.g., ICT, psychology, sociology, humanities, communication theory, sustainable energy, circular economy, entrepreneurship, etc.).